2017
DOI: 10.1001/jamasurg.2017.0098
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Ratio of Fresh Frozen Plasma to Red Blood Cells During Massive Transfusion and Survival Among Patients Without Traumatic Injury

Abstract: High FFP:RBC transfusion ratios are applied mostly to patients without trauma, who account for nearly 90% of all massive transfusion events. Thirty-day survival was not significantly different in patients who received a high FFP:RBC ratio compared with those who received a low ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 17 publications
2
42
0
3
Order By: Relevance
“…Given the extensive literature and debate on the value of FFP in trauma, it may be more beneficial to use gelsolin in isolation to scavenge excess actin and restore DNase activity. Indeed, low plasma gelsolin levels on admission to hospital following trauma have been associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Given the extensive literature and debate on the value of FFP in trauma, it may be more beneficial to use gelsolin in isolation to scavenge excess actin and restore DNase activity. Indeed, low plasma gelsolin levels on admission to hospital following trauma have been associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…80,81 A large retrospective review of experience before and after implementation of 1:1 resuscitation failed to show a mortality benefit. 82 The Canadian consensus conference on massive transfusion recommended an RBC:plasma ratio of 2:1 followed by transition to laboratory-guided administration of blood components as soon as possible. 83 The standard approach outlined below, which is based on expert consensus, is applicable to most large adult hospitals.…”
Section: In Bleeding Patients In Need Of Red Blood Cell Transfusionmentioning
confidence: 99%
“…Patients undergoing surgery, including cardiothoracic and gastrointestinal (GI) surgery, are the greatest recipients of MTs (Halmin et al, 2016;Ruseckaite et al, 2017). Despite being the focus of most of the research, trauma patients receive <20% of all MTs (Zatta et al, 2014;Halmin et al, 2016;Mesar et al, 2017;Ruseckaite et al, 2017). Although hospitals often maintain emergency blood supplies for use in obstetrics, and this drives many inventory management decisions, major post-partum haemorrhage requiring MT is fortunately rare -in the UK, this has been reported to be just 23 cases per 100 000 maternity admissions (Green et al, 2016b), and obstetric patients receive <6% of all MTs (Halmin et al, 2016;Ruseckaite et al, 2017).…”
Section: The Epidemiology Of Massive Transfusionsmentioning
confidence: 99%
“…() conducted a retrospective study of 62 trauma and 63 non‐trauma patients and found that transfusion ratio was not associated with mortality for either patient cohort. In another retrospective study of both trauma and non‐trauma patients, of 865 patients who received MTs (defined as >10 units of RBCs in 24 h) over 4 years, 767 (88·7%) were classified as non‐trauma, and there was no difference in 30‐day mortality comparing higher ratios to lower ratios (Mesar et al, ). When considering individual non‐trauma subgroups, there was a reduced risk of mortality for higher ratios in the vascular subgroup and a reduced risk of mortality for lower ratios for the medicine and general surgery subgroups (Baumann Kreuziger et al, ).…”
Section: Blood Component and Coagulation Factor Supportmentioning
confidence: 99%